An empirical study on the evolution and driving factors of energy-related carbon emissions in the Yangtze River Economic Belt - Zhu, Yi; Liu, Xieqihua; Feng, Chao; Zhang, Tao; Wang, Xi (Frontiers in Environmental Science, 2025)
This study analyzes energy-related carbon emissions in the Yangtze River Economic Belt (YREB) from 2000 to 2022 using regional energy consumption data and IPCC guidelines. The Mann-Kendall trend test and mutation point detection methods are applied to examine emission trends and structural shifts. The Kaya identity and Logarithmic Mean Divisia Index (LMDI) approach are used to decompose the impacts of energy structure, economic activity, population, and energy intensity on carbon emissions across subregions. The results show that since 2000, the growth rate of carbon emissions across the YREB has slowed significantly, with annual growth remaining below 2.5% since 2012. The energy mix has improved, with coal’s share decreasing from 77% to 69%, while natural gas and electricity’s combined share grew from 1% to 4%. Regionally, emissions in the Midstream reaches have peaked and are declining, while the Upstream reaches are nearing their peak. Although the Downstream reaches have not yet peaked, their emission growth has markedly decelerated. Overall, energy intensity and structural optimization have suppressed emissions, while economic growth and population expansion remain the dominant drivers. These findings highlight the need for continued optimization of both energy and industrial structures, with differentiated carbon reduction strategies tailored to each subregion’s unique characteristics and development stages within the YREB.